PENCIPTAAN IKLAN LAYANAN MASYARAKAT DENGAN TEMA PENGELOLAAN SAMPAH RUMAH TANGGA - Sukartika, I Wayan Pradnya; Yasa, Desak Putu Yogi Antari Tirta; Payuyasa, I Nyoman (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
The more developed human civilization, the more human population in it. It turns out that the impact of the large human population also produces a lot of waste, the waste is produced from human activities, ranging from domestic waste, commercial waste, to agricultural waste. However, the waste produced by humans is not handled properly, so that it has an impact on the surrounding environment. Such as pollution of coastal beaches, pollution of lakes to the accumulation of waste in landfills. One solution is to handle the large amount of waste with Waste Management, the waste management that must be done is household waste management. This is because the waste that pollutes the environment comes from sources, the sources here mostly come from household waste. Around 44.13%. So in this journal the author presents how the process of creating the work of Household Waste Management Community Advertisements, which is taken from in-depth research that occurs in society.